Implikasi Waktu dan Temperatur Pengeringan Pada Mutu Tepung Wortel (Daucus Carota L) - Risnadi Irawan; Mustafa Kamal; Hanif Muchdatul Ayunda; Azhar (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The temperature and time of evaporation are very influential in the production of carrot flour to determine the effect of temperature, drying time and the interaction between the effect of temperature and drying time on the quality of carrot flour produced. The aim of this study was to determine the effect of temperature, drying time and the interaction between the effect of temperature and drying time on the quality of carrot flour produced. In this study, two replications of the Rancangan Acak Lengkap (RAL) factorial were used for data collection and analysis. The three levels of temperature (60, 70 and 80 degrees Celsius) and the three levels of drying time are the variables used.5, 6 and 7 hours. The parameters analysed were water content, ash content, yield of colour organoleptic test, aroma, beta-carotene. The results of the study can be concluded that the effect of temperature has a very significant effect on the analysis of ash content and yield has no significant effect on the analysis of water content and organoleptic tests of colour and aroma. The analysis of yield and organoleptic test of colour is strongly influenced by drying time, but the analysis of water content, ash content and organoleptic test of aroma is not much influenced. The interaction of temperature and drying time has a very significant effect on the analysis of ash content and yield and has no significant effect on the analysis of water content and organoleptic tests of colour and aroma.